2014
DOI: 10.1021/pr400880s
|View full text |Cite
|
Sign up to set email alerts
|

Shotgun Proteomic Analysis Unveils Survival and Detoxification Strategies byCaulobacter crescentusduring Exposure to Uranium, Chromium, and Cadmium

Abstract: The ubiquitous bacterium Caulobacter crescentus holds promise to be used in bioremediation applications due to its ability to mineralize U(VI) under aerobic conditions. Here, cell free extracts of C. crescentus grown in the presence of uranyl nitrate [U(VI)], potassium chromate [Cr(VI)], or cadmium sulfate [Cd(II)] were used for label-free proteomic analysis. Proteins involved in two-component signaling and amino acid metabolism were up-regulated in response to all three metals, and proteins involved in aerobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 67 publications
4
40
0
Order By: Relevance
“…Given that similar numbers of unique insertions are present in our data sets compared to those of other Tn-seq studies, we believe that the low fitness values are indicative of the fact that C. crescentus has a broad and relatively graded response to U toxicity. Consistent with this notion, previous proteomic and transcriptomic studies (23,24) also indicate that a small group of specialized genes cannot account for U resistance. Instead, the response occurs on a global level, involving many genes from different pathways serving functions that may act redundantly to mitigate U toxicity.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…Given that similar numbers of unique insertions are present in our data sets compared to those of other Tn-seq studies, we believe that the low fitness values are indicative of the fact that C. crescentus has a broad and relatively graded response to U toxicity. Consistent with this notion, previous proteomic and transcriptomic studies (23,24) also indicate that a small group of specialized genes cannot account for U resistance. Instead, the response occurs on a global level, involving many genes from different pathways serving functions that may act redundantly to mitigate U toxicity.…”
Section: Discussionsupporting
confidence: 55%
“…In summary, our Tn-seq screen for genes involved in detoxification and stress regulation during U exposure by C. crescentus has yielded several novel targets whose identity and function had previously remained elusive through other types of omics analyses (23,24). The results highlight that genes necessary for longer-term growth and survival under U stress do not significantly overlap those that are upregulated in response to acute U stress.…”
Section: Figmentioning
confidence: 96%
See 2 more Smart Citations
“…C. crescentus exposed to high levels of U(VI) arrested cell cycle progression; the stalked-cell transition and the initiation of DNA replication were blocked in swarmer cells, while cell division was inhibited in stalked and predivisional cells. Recent proteomic analysis indicated that the levels of two master cell cycle regulators, CtrA and DnaA, were significantly reduced during U(VI) exposure (41). During the C. crescentus cell cycle, the abundance of these regulators is tightly controlled in order to precisely regulate the timing of DNA replication.…”
Section: Discussionmentioning
confidence: 99%